Impact of KNO3 Primed Seeds on the Performance of Late Sown Sesame (Sesamum indicum L.) - Kumar, Sunil; Hemantaranjan, A.; Mondal, Sananda; Bose, Bandana (International Journal of Bio-resource and Stress Management, 2023)
In the present piece of work the effects of seed priming with KNO3 on late sown sesame crop (Sesamum indicum) var. T-4 (V1), T-12 (V2) and Shekhar (V3) in respect of germination, physiomorphological, biochemical and yield parameters were observed. The treatments comprised of KNO3 [10 mM (T1), 15 mM (T2)] and distilled water (DW) primed sets (T0). The results showed that the KNO3 treatment promoted germination percentage, root and shoot length, fresh and dry weights of seedling, catalase, peroxidase and proline content as well as yield attributes like number of capsules plant-1, number of seeds capsule-1, test weight (1000 seed weight in g) and yield plant-1 (g). After 80 h, the highest germination percentage was recorded in 15 mM KNO3 (T2) primed seeds of Sesamum indicum var. T-4, T-12 and Shekhar. The average of root length, shoot length, fresh weight, and dry weight was recorded highest in treatment T2 in comparison to distilled water primed seeds (control) at 25 DAS in all varieties i.e., T-4, T-12 and Shekhar respectively. Yield attributes like number of capsules plant-1, number of seeds capsule-1, test weight and yield plant-1 were also highest in treatment T2 in all varieties V1, V2 and V3 respectively. Variety V1 and treatment T2 recorded the highest values of catalase, peroxidase and proline content followed by variety V3 and V2 and treatment T1 and T0 at 45 DAS respectively. It had been found that seed priming with KNO3 ameliorate the effect of late sowing.